PENGARUH PROFESIONALISME, BUDAYA ORGANISASI, PENGEMBANGAN KARIER, DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR - Trya Dewi Widowati (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the significance of the influence of professionalism, organizational culture, career development or organizational commitment partially or simultaneously to the Organization Citizenship Behavior at the District Office employees Gondangrejo Karanganyar. In conclusion, the results of the data analysis we concluded there was a significant effect of professionalism, organizational culture, career development and organizational commitment on Organizational Citizenship Behavior on District Office employees Gondangrejo Karanganyar. The results of the F test analysis we concluded there was a significant effect of independent variables namely professionalism, organizational culture, career development, and organizational commitment to the dependent variable is the Organizational Citizenship Behavior in the District Office employees Gondangrejo Karanganyar. Keywords: professionalism, organizational culture, career development, organizational commitment, organization citizenship behavior